Self-ownership and Spontaneously-Evolved Order. The Core of the Max Stirner’s Individualist Anarchism - Chmieliński, Maciej (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
Author of the article argues that in spite of a subjectivist nature of Max Stirner’s thought which is distinct from libertarianism, there’s a strong intellectual affinity between anarchist wing of it and Stirner’s conception. This position is based on three crucial arguments. First, Stirner’s opus magnum The Ego and Its Own is one of the most zealous declarations of social individualism based upon the idea of self-ownership. Second, the Archimedean point of both analyzed political philosophies is the idea of spontaneous order, i.e. the conviction that the efficient cooperation between egoistic individuals – and thus not mediated by any external constraints - is possible. Third, there are important historical connections between Stirner’s conception and representatives of individualistic or libertarian anarchism.